Machine learning-driven investigation of key flavor factors in pale lager beer fermentation samples and their evolution mechanisms during fermentation - Jiang Xie; Ruiyang Yin; Xin Yuan; Bofeng Zhong; Liyun Guo; Yumei Song; Wenjing Tian; Yiyu Chen; Keyi Ling; Dongrui Zhao; Baoguo Sun; Jinyuan Sun; et al. (Food Chemistry, 2026)

Highly efficient H2S absorption and conversion by cyclohexanone-enhanced ionic liquid composite systems - Xiankun Wu; Huiqin Xu; Keyi Huang; Wentao Zheng; Youting Wu; Xiaomin Zhang (Chemical Engineering Journal, 2026)

Seasonal eco-hydrological dynamics of China’s Dongting and Poyang Lake wetlands: A 26-year meta-analysis - Shafeeq Ur Rahman; Jing-Cheng Han; Ghulam Yasin; Keyi Wang; Yulei Xie; Yuefei Huang (Process Safety and Environmental Protection, 2026)

One-step treatment of refractory organic pollutants from landfill leachate: alternating magnetic field synergies persulfate activation and in-situ coagulation - Dawei Wang; Yingying Li; Yilan Jiang; Yihan Zhu; Na Huang; Keyi Gao; Jiarong Li; Shijie You (Chemical Engineering Journal, 2026)

Coupling upconversion effect with p-n heterojunction on TiAl6V4 to eradicate bacterial biofilms - Keyi Yao; Lixuan Huang; Jie Shao; Junyu Dong; Junhua Xu; Yongsheng Liu; Sze Wing Cheung; Lin Xiang; Xuemei Zhou (Chemical Engineering Journal, 2026)

Post-transcriptional regulation of ABCB1 by miR-34-5p is associated with emamectin benzoate susceptibility in Spodoptera frugiperda - Congsai Wang; Jingdong Li; Zikun Wang; Liying Wu; Huiling Huang; Yunkun Zi; Binrui Bai; Keyi Chen; Hongsong Chen; Huihua Tan; Yutao Xiao; Kaikai Mao (Pesticide Biochemistry and Physiology, 2026)

Self-assembled and reversibly esterified hierarchical networks enable tough, anti-swelling and recyclable nanocomposite hydrogel - Zhengxu Jin; Ying Chen; Feihong Hu; Huizhu Wang; Qianyue Zeng; Keyi Yang; Hong Chen; Xiaoming Huang; Jing Xie; Jianshu Li (Chemical Engineering Journal, 2026)

Corrigendum to ‘Constitutive overexpression of ATP-binding cassette transporters contributes to emamectin benzoate resistance in Spodoptera frugiperda’ [Pesticide Biochemistry and Physiology, 219 (2026) 106980] - Congsai Wang; Zikun Wang; Jingdong Li; Yunkun Zi; Huiling Huang; Binrui Bai; Keyi Chen; Jing Wang; Hongsong Chen; Huihua Tan; Kaikai Mao (Pesticide Biochemistry and Physiology, 2026)

Vertical distribution pattern, preferred life strategies and environmental response of prokaryotic microbiome in the eastern tropical indian ocean - Jinfeng Wang; Wenbin Zhao; Shaodong Zhu; Keyi Huang; Yulin Zhang; Haojin Cheng; Qin Ma; Derui Song; Jiwen Liu; Xiao-Hua Zhang; Xiaolei Wang (Marine Environmental Research, 2026)

Constitutive overexpression of ATP-binding cassette transporters contributes to emamectin benzoate resistance in Spodoptera frugiperda - Congsai Wang; Zikun Wang; Jingdong Li; Yunkun Zi; Huiling Huang; Binrui Bai; Keyi Chen; Jing Wang; Hongsong Chen; Huihua Tan; Kaikai Mao (Pesticide Biochemistry and Physiology, 2026)

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

UVB enhances SLC6A15-mediated phenylalanine transport to promote melanogenesis - Shu Zhou; Yujie Ouyang; Yibo Hu; Xixia Dai; Ling Jiang; Chuhan Fu; Yaqing Wen; Jiangfeng Huang; Keyi Zhang; Jing Chen; Qinghai Zeng (Journal of Photochemistry and Photobiology B: Biology, 2026)

Microbial community assembly and functional adaptation of urease-producing bacteria in oil reservoirs: Driven by phase heterogeneity and selective enrichment - Yanlong He; Keyi Liu; Tengda Huang; Weibo Wang; Xiaoqi Zhang; Lu Bai; Junxi Zhang; Hai Huang (Journal of Environmental Chemical Engineering, 2025)

From heterogeneity to prognosis: understanding the complexity of tertiary lymphoid structures in tumors - Yingying Wang; Dongyan Zhang; Xueping Huang; Guohao Wu; Chuanbao Wang; Jun Li; Song Wang; Xinmiao Xian; Bo Fu; Keyi Li (Molecular Biology Reports, 2025)

Application of deep learning for multi-scale behavioral analysis in SNCA E46K Parkinson’s disease drosophila - Keyi Dong; April Burch; Kang Huang (Cognitive Neurodynamics, 2025)

Emergence and genomic characterization of Vibrio parahaemolyticus serotype O10:K4 from seafood-linked diarrheal cases in Zhejiang, China (2016–2023) - Jiewen Huang; Zhen Zhang; Qingtian Li; Jiancai Chen; Lingling Mei; Xiaojuan Qi; Lili Chen; Junyan Zhang; Chao Lv; Min Li; Honghu Chen; Yanjun Zhang; et al. (Food Research International, 2025)

Government performance evaluation and energy efficiency: evidence from a quasi-natural experiment on the removal of GDP evaluations in Chinese counties - Xinshuo Hou; Guangxiang Zheng; Keyi Huang; Dongyang Li (Environment, Development and Sustainability, 2025)

Selective enrichment of comammox over NOB Nitrospira on biofilm in low-oxygen integrated fixed-film activated sludge system - Yunlong Li; Jin Chen; Bowen Wang; Naif Abdullah Al-Dhabi; Zimin Chai; Keyi Zhang; Shujun Huang; Wangwang Tang; Maosheng Zheng (Journal of Environmental Chemical Engineering, 2025)

Double special bodyguard: Selenium-enhanced loop-mediated isothermal amplification combined with CRISPR/Cas12a biosensing strategy - Keyi Long; Tiao Han; Wenxi Hu; Mei Yang; Danqun Huo; Zhen Huang; Changjun Hou (Analytica Chimica Acta, 2025)

A hydroxyl coumarin-chalcone-based fluorescent probe for sensing copper ions in plant and living cells - Keyi Li; Yan Huang; Yatong Sun; Yiping Zhang; Yan Zhang; Baosheng Ren; Duxia Cao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Heatwave enhance the adaptability of Chlorella pyrenoidosa to zinc oxide nanoparticles: Regulation of interfacial interactions and metabolic mechanisms - Keyi Huang; Hui Zeng; Qixing Zhou (Water Research, 2025)

Application of a fluorescent probe exhibiting a large stokes shift after the precise detection of hydrazine in plants, foods and living cells - Yan Zhang; Yan Huang; Guiyi Yang; Haotian Xin; Keyi Li; Lei Wang; Shangcong Gu; Baosheng Ren; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2025)

Exploration the effect of air pollution on the incidence of myasthenia gravis: An empirical study from Chengdu - Rui Zhou; Tianjun Li; Keyi Tian; Lei Huang (Atmospheric Pollution Research, 2025)

Effectively increase the L(+)-isomer proportion of ethyl lactate in Baijiu by isolating and applying L(+)-lactic acid-producing bacteria - Zhiqiang Ren; Lvchang Liu; Tuoxian Tang; Keyi Huang; Zhiguo Huang (Food Bioscience, 2025)

Enterovibrio qingdaonensis sp. nov. and Enterovibrio gelatinilyticus sp. nov., two marine bacteria isolated from surface seawater of Qingdao offshore - Keyi Huang; Yi Liu; Yan Wang; Pingping Zhang; Haojin Cheng; Jinfeng Wang; Wanjia Tong; Wang Xiaolei; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2025)

Decoding PTEN: from biological functions to signaling pathways in tumors - Xueping Huang; Dongyan Zhang; Di Zhang; Jianran Guo; Guohao Gu; Yingying Wang; Guohao Wu; Chuanbao Wang; Bo Fu; Keyi Li (Molecular Biology Reports, 2024)

From spent lithium-ion batteries to functional materials: A review - Tingjin Zhou; Keyi Lin; Yusen Wu; Baojia Qin; Jie Zhu; Zhe Huang; Zhenming Xu; Jujun Ruan (Resources, Conservation and Recycling, 2024)

Separation cathode materials from current collectors of spent lithium-ion battery through low-energy mechanical friction technology - Keyi Lin; Yusen Wu; Ying Shen; Yanrui Zheng; Zicheng Wang; Jinjuan Chen; Taoli Wu; Jie Zhu; Zhe Huang; Baojia Qin; Jujun Ruan (Resources, Conservation and Recycling, 2024)

Near-infrared and multifunctional fluorescent probe enabled by cyanopyridine cyanine dye for bisulfite recognition and biological imaging - Shangcong Gu; Yan Huang; Xinxin Li; Haotian Xin; Haoran Mu; Yan Zhang; Keyi Li; Guiyi Yang; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2024)

Corrigendum to “Microcystin-LR improves anti-tumor efficacy of oxaliplatin through induction of M1 macrophage polarization” [Toxicon 2024 May 28;243(0):107723] - Keyi Li; Minzhu Yang; Yuxin Dai; Jinyan Huang; Peng Zhu; Qiuzhen Liu (Toxicon, 2024)

Microcystin-LR improves anti-tumor efficacy of oxaliplatin through induction of M1 macrophage polarization - Keyi Li; Minzhu Yang; Yuxin Dai; Jinyan Huang; Peng Zhu; Liu Qiuzhen (Toxicon, 2024)

Geochemical and U-Pb isotopic insights into uranium (U) enrichment in the soil around a nuclear fuel element plant, in Southwest China - Xin Cheng; Jianing Sun; Kai Ling; Keyi Zhong; Bolin Shao; Lan Li; Shanshan Zhao; Yi Huang; Hao Song; Bo Cheng (Ore and Energy Resource Geology, 2024)

Suppression of ETI by PTI priming to balance plant growth and defense through an MPK3/MPK6-WRKYs-PP2Cs module - Dacheng Wang; Lirong Wei; Ting Liu; Jinbiao Ma; Keyi Huang; Huimin Guo; Yufen Huang; Lei Zhang; Jing Zhao; Kenichi Tsuda; Yiming Wang (Molecular Plant, 2023)

Recovery of pure lead and preparation of nano-copper from waste glass diodes via a clean and efficient technology of step-by-step vacuum evaporation-condensation - Taiyu Huang; Keyi Lin; Xiao Tan; Jujun Ruan (Resources, Conservation and Recycling, 2023)

Enabling efficiency-driven and low-impact water management from robust decision making: A risk- and robustness-based multi-objective decision support model - Yang Zhou; Bing Li; Jingcheng Han; Guojian He; Keyi Wang; Chunjiang An; Yuefei Huang (Journal of Cleaner Production, 2023)

A synthesis of Carboniferous stratigraphy in Xinjiang, Northwest China with emphasis on regional and global correlations - Yong Tang; Xunyan Ye; Xiatian Wang; Xing Huang; Zhangshuai Hou; Keyi Hu; Sunrong Yang; Ying Li; Feifei Zhang; Shuzhong Shen; Xiangdong Wang (Journal of Asian Earth Sciences, 2023)

Short-term effects of ambient particulate matter (PM1, PM2.5 and PM10) on influenza-like illness in Guangzhou, China - Jianyun Lu; Keyi Wu; Xiaowei Ma; Jing Wei; Zelin Yuan; Zhiwei Huang; Weidong Fan; Qi Zhong; Yining Huang; Xianbo Wu (International Journal of Hygiene and Environmental Health, 2023)

Potential of granular complexes of lime and montmorillonite for stabilizing soil cadmium and the underlying mechanisms - Gaoxiang Huang; Keyi Huang; Xingxiang Wang; Wuxing Shu; Wenjing Ren; Peng Wang; Hua Zhang; Minghua Nie; Mingjun Ding (Environmental Pollution, 2023)

Astronomical Tide and Storm Surge Signals Observed in an Isolated Inland Maar Lake Near the Coast - Mingming Li; Chunyan Li; Lingling Xie; Wei Huang; Quanan Zheng; Keyi Tan; Yingbin Hong (Journal of Marine Science and Engineering, 2021)
Aimed at the explanation of clear tidal signal and storm surge signals in a closed inland lake near the coast (the Huguangyan Lake), this work uses a combined approach with observations and model experiments. Huguangyan Lake is a closed inland freshwater coneless volcanic crater lake near the coast in tropical southern China, less than 5 km from an estuary. It has a diameter of about 1.5 km and relatively deep water of up to 20 m. Bottom pressure was measured from an acoustic Doppler current profiler (ADCP) for 10 days in September 2018 and 10 days in January 2019. The observations encompass the period of Typhoon Mangkhut, which passed the region when it made its landfall. The time series demonstrate clear tidal and subtidal signals. The tidal signal remains even if we exclude the barometric pressure effect. Interestingly, the lake has no surface connection with the ocean. The astronomical tide has an amplitude of about 2 cm. The major tidal signals include the principal solar semidiurnal (S2) and lunisolar (K1) constituents. During the passage of Typhoon Mangkhut, the water level variability inside the lake increased by an order of magnitude (>0.3 m). To examine whether the lake water level change was due to the natural oscillations inside the lake (or seiche), a numerical wind-driven hydrodynamics model was designed using the 3-D Finite Volume Community Ocean Model (FVCOM). The results show that a small first-order seiche can be generated, but only with a time scale of minutes and with a magnitude much smaller than the observed surface elevation changes. This excludes any measurable seiche and the observed surface elevation change inside the lake cannot be wind-driven. Moreover, tides inside the lake are not generated by tidal potential, as the lake is too small for having a locally generated tide. The main result of our study has therefore excluded the local tidal-generating force, wind-driven seiche, and barometric effect, as possible causes of the lake oscillation which has tidal and subtidal signals. The subtidal variation is at least one order of magnitude greater than tides inside the lake and is caused by weather-induced overall coastal ocean water level oscillations transmitted into the lake through groundwater connection. All these lead to the major conclusion that the lake is connected to the coastal ocean through groundwater.

Discrimination of Tourette Syndrome Based on the Spatial Patterns of the Resting–State EEG Network - Keyi Duan; Qian Wu; Yuanyuan Liao; Yajing Si; Joyce Chelangat Bore; Fali Li; Qin Tao; Li Lin; Wei Lei; Xudong Hu; Dezhong Yao; Changfu Pei; et al. (Brain Topography, 2021)

Statistical analysis of mesoscale eddy propagation velocity in the South China Sea deep basin - Runqi Huang; Lingling Xie; Quanan Zheng; Mingming Li; Peng Bai; Keyi Tan (Acta Oceanologica Sinica, 2020)

Stability of soil organic carbon and potential carbon sequestration at eroding and deposition sites - Wenming Ma; Zhongwu Li; Keyi Ding; Bin Huang; Xiaodong Nie; Yinmei Lu; Haibin Xiao; Guangming Zeng (Journal of Soils and Sediments, 2016)